The Reality Of Using Educational Technology In Teaching Mathematics From The Point Of View Of Mathematics Teachers In Amman (Journal Of Educational and Psychological Researches, 2022)
The study aims to identify the reality of the use of educational technology in the teaching of mathematics from the point of view of mathematics teachers in Amman, where the researcher used the descriptive survey method. The sample included (67) female teachers working in public schools in Amman. In order to achieve the objectives of the study, the researcher used the questionnaire as a tool to collect data. The study concluded that many educational techniques are not available from the point of view of the study sample. Mathematics teachers also found that there are many obstacles that prevent the use of educational techniques in schools, most notably the lack of courses offered to teachers on the use of teaching techniques in teaching mathematics, the lack of the necessary techniques to teach mathematics, classrooms are not commensurate with the use of techniques. The results indicated that the significance level is greater than (0.05) in the two dimensions of the research tool, indicating that there are no statistically significant differences in the extent of employing teaching techniques in teaching mathematics. The study recommended the need to provide equipment and tools to activate the techniques of education in schools.